High-temperature Reliability of 1 200 V SiC Power MOSFETs - DENG Xiaochuan; CHEN Xixi; WANG Yiyu; SHEN Huajun; TANG Yachao; GAO Yunbing (Kongzhi Yu Xinxi Jishu)
High-temperature reliability is currently a key issue limiting the application of SiC MOSFET devices in high-temperature environment. It intruduced the DC electrical performance of 1 200 V SiC MOSFETs, which was fabricated based on domestic process platform, and then its high-temperature reliability was analyzed after high temperature gate-bias test (HTGB) and high temperature reversebias test (HTRB). The experimental results indicated that after 168 hours HTGB and HTRB tests, breakdown voltage of the fabricated samples is more than 1 200 V and the variations of threshold voltage and on-resistance are less than 15% respectively, suggesting good robustness of these devices. It also confirms the feasibility of the design, process and fabrication of domestic 1 200 V SiC MOSFETs.